RP-HPLC determination of dissociation constant using solely aqueous mobile phase - Volná, Tereza; Motyka, Kamil; Hlaváč, Jan (Journal of pharmaceutical and biomedical analysis, 2017)
The proposed HPLC method using solely or nearly 100% aqueous mobile buffer as mobile phase offers fast determination of dissociation constant for compounds in relatively wide range of lipophilicity (log P from -2.26 to 2.26). The dissociation constant value for simpler chemical compounds can be determined via only 8 chromatographic runs. The number of needed chromatographic separations depends on the structural complexity of the tested compound. Moreover, the proposed method does not require a measurement of Yasuda-Shedlovsky extrapolation that includes several pKa determinations in solutions with different methanol content which speeds up considerably the procedure. The methodology is suitable for evaluation of large series of drug candidates, which can be present as complex mixtures and in small amounts.
Keywords: Chromatography, High Pressure Liquid; High-throughput measurement; Water; Reversed phase; Chromatography, Reverse-Phase; HPLC; Dissociation constant; vysokoúčinná kapalinová chromatografie; voda; chromatografie s reverzní fází